Universal routine HPV vaccination for young girls in Uganda: a review of opportunities and potential obstacles - Banura, Cecily; Mirembe, Florence M.; Katahoire, Anne R.; Namujju, Proscovia B.; Mbidde, Edward K. (Infectious Agents and Cancer, 2012)
This article reviews the existing realities in Uganda to identify opportunities and potential obstacles of providing universal routine HPV vaccination to young adolescent girls. Cervical cancer is a public health priority in Uganda where it contributes to about 50–60% of all female malignancies. It is associated with a dismal 5-year relative survival of approximately 20%. With adequate financial resources, primary prevention through vaccination is feasible using existing education and health infrastructure. Cost-effectiveness studies show that at a cost of US$2 per dose, the current vaccines would be cost effective. With optimal (≥70%) coverage of the target population, the lifetime risk of cervical cancer could be reduced by >50%. Uganda fulfils 4 out of the 5 criteria set by the WHO for the introduction of routine HPV vaccination to young adolescent girls. The existing political commitment, community support for immunization and the favorable laws and policy environment all provide an opportunity that should not be missed to introduce this much needed vaccine to the young adolescent girls. However, sustainable financing by the government without external assistances remains a major obstacle. Also, the existing health delivery systems would require strengthening to cope with the delivery of HPV vaccine to a population that is normally not targeted for routine vaccination. Given the high incidence of cervical cancer and in the absence of a national screening program, universal HPV vaccination of Ugandan adolescent girls is critical for cervical cancer prevention.
Keywords: HPV vaccination; Young girls; Uganda